Ipilimumab alone or ipilimumab plus anti-PD-1 therapy in patients with metastatic melanoma resistant to anti-PD-(L)1 monotherapy: a multicentre, retrospective, cohort study. Issue 6 (June 2021) - Pires da Silva, Ines; Ahmed, Tasnia; Reijers, Irene L M; Weppler, Alison M; Betof Warner, Allison; Patrinely, James Randall; Serra-Bellver, Patricio; Allayous, Clara; Mangana, Joanna; Nguyen, Khang; Zimmer, Lisa; Trojaniello, Claudia; et al.
Summary: Background: Anti-PD-1 therapy (hereafter referred to as anti-PD-1) induces long-term disease control in approximately 30% of patients with metastatic melanoma; however, two-thirds of patients are resistant and will require further treatment. We aimed to determine the efficacy and safety of ipilimumab plus anti-PD-1 (pembrolizumab or nivolumab) compared with ipilimumab monotherapy in patients who are resistant to anti-PD-(L)1 therapy (hereafter referred to as anti-PD-[L]1). Methods: This multicentre, retrospective, cohort study, was done at 15 melanoma centres in Australia, Europe, and the USA. We included adult patients (aged ≥18 years) with metastatic melanoma (unresectable stage III and IV), who were resistant to anti-PD-(L)1 (innate or acquired resistance) and who then received either ipilimumab monotherapy or ipilimumab plus anti-PD-1 (pembrolizumab or nivolumab), based on availability of therapies or clinical factors determined by the physician, or both. Tumour response was assessed as per standard of care (CT or PET–CT scans every 3 months). The study endpoints were objective response rate, progression-free survival, overall survival, and safety of ipilimumab compared with ipilimumab plus anti-PD-1. Findings: We included 355 patients with metastatic melanoma, resistant to anti-PD-(L)1 (nivolumab, pembrolizumab, or atezolizumab), who had been treated with ipilimumab monotherapy (n=162 [46%]) or ipilimumab plus anti-PD-1 (n=193 [54%]) between Feb 1, 2011, and Feb 6, 2020. At a median follow-up of 22·1 months (IQR 9·5–30·9), the objective response rate was higher with ipilimumab plus anti-PD-1 (60 [31%] of 193 patients) than with ipilimumab monotherapy (21 [13%] of 162 patients; p<0·0001). Overall survival was longer in the ipilimumab plus anti-PD-1 group (median overall survival 20·4 months [95% CI 12·7–34·8]) than with ipilimumab monotherapy (8·8 months [6·1–11·3]; hazard ratio [HR] 0·50, 95% CI 0·38–0·66; p<0·0001). Progression-free survival was also longer with ipilimumab plus anti-PD-1 (median 3·0 months [95% CI 2·6–3·6]) than with ipilimumab (2·6 months [2·4–2·9]; HR 0·69, 95% CI 0·55–0·87; p=0·0019). Similar proportions of patients reported grade 3–5 adverse events in both groups (59 [31%] of 193 patients in the ipilimumab plus anti-PD-1 group vs 54 [33%] of 162 patients in the ipilimumab group). The most common grade 3–5 adverse events were diarrhoea or colitis (23 [12%] of 193 patients in the ipilimumab plus anti-PD-1 group vs 33 [20%] of 162 patients in the ipilimumab group) and increased alanine aminotransferase or aspartate aminotransferase (24 [12%] vs 15 [9%]). One death occurred with ipilimumab 26 days after the last treatment: a colon perforation due to immune-related pancolitis. Interpretation: In patients who are resistant to anti-PD-(L)1, ipilimumab plus anti-PD-1 seemed to yield higher efficacy than ipilimumab with a higher objective response rate, longer progression-free, and longer overall survival, with a similar rate of grade 3–5 toxicity. Ipilimumab plus anti-PD-1 should be favoured over ipilimumab alone as a second-line immunotherapy for these patients with advanced melanoma. Funding: None.